UPAYA KEPALA SEKOLAH UNTUK MENINGKATKAN KEMAMPUAN GURU DALAM PENGGUNAAN KOMPUTER MELALUI PENERAPAN METODE PEER TEACHING DI SMP 5 KOTA BOGOR - Warsadi . (FKIP UNIVERSITAS PAKUAN, 2020)
THE EFFORTS OF HEADMASTER TO IMPROVE TEACHERS 'ABILITY IN COMPUTER USE THROUGH THE APPLICATION OF THE PEER TEACHING METHOD IN JUNIOR HIGH SCHOOL (SMP NEGERI 5), BOGOR CITYThis research was motivated by the lack of teachers' ability to use computers. This can affect the process and quality of learning in the classroom. Therefore a school principal must strive to improve the competence and ability of teachers in using computers, in this case the effort made is to use the Peer Teaching method. This study aims to (1) determine that the application of the peer teaching method can improve the ability of teachers of SMP Negeri 5 Bogor in using computers. (2) describes the process of increasing the ability of teachers at SMP Negeri 5 Bogor in using computers after the peer teaching method was applied. (3) measuring the amount of improvement in the ability of teachers at SMP Negeri 5 Bogor in using computers after the peer teaching method was applied. The results of this study indicate that before the application of the peer teaching method on computer use at SMP Negeri 5 Bogor, of the 46 teachers in SMP 5 Bogor, there were 12 teachers who were not able to use computers. Then an effort was made to improve the teacher's ability to use computers, namely through the application of the peer teaching method. still unable, then improvements were made in cycle II so that there was a significant increase in the presence of 6 teachers who became proficient in using computers and 6 teachers who were able to use computers. From the above description, the researcher concludes that the application of the peer teaching method used can improve the ability of teachers to use computers, therefore the researcher suggests that the application of the peer teaching method needs to be socialized and used in schools in the Bogor City Education Office.